Expressão de receptores de inositol 1,4,5-trifosfato do tipo 3 é um evento final comum ao desenvolvimento do carcinoma hepatocelular - Rodrigo Machado Florentino (2020)
Background: Hepatocellular carcinoma (HCC) is the second leading cause of cancer death worldwide. Several types of chronic liver disease predispose to HCC, and several different signaling pathways have been implicated in its pathogenesis, but no common molecular event has been identified. Calcium (Ca2+) signaling regulates the proliferation of both normal hepatocytes and liver cancer cells and can be a target in the HCC development. Objective: We investigated the role of the protein involved on the intracellular Ca2+ signaling in HCC. Design: Expression analyses of the type 3 isoform of the inositol 1, 4, 5-trisphosphate receptor (ITPR3) in human liver samples, liver cancer cells and mouse liver were combined with the evaluation of DNA methylation profiles of ITPR3 promoter in HCC and characterization of the effects of ITPR3 expression on cellular proliferation and apoptosis. The effects of de novo ITPR3 expression on calcium signaling and liver growth were evaluated in mice. Results: ITPR3 was absent or expressed in low amounts in hepatocytes from normal liver, but was expressed in HCC specimens from three independent patient cohorts, regardless of the underlying cause of chronic liver disease, its increased expression level was associated with poorer survival. The ITPR3 gene was heavily methylated in control liver specimens but was demethylated at multiple sites in specimens of patient with HCC. Administration of a demethylating agent in a mouse model resulted in ITPR3 expression in discrete areas of the liver, and Ca2+ signalling was enhanced in these regions. In addition, cell proliferation and liver regeneration were enhanced in the mouse model, and deletion of ITPR3 from human HCC cells enhanced apoptosis. Conclusions: These results provide evidence that de novo expression of ITPR3 typically occurs in HCC and may play a role in its pathogenesis.